Usage of thermoelectric level indicators in the monitoring system of WWER-1000 reactor during severe accidents - Кузьменко, Виталий Павлович; Сиренко, Николай Иванович; Мовчан, Анатолий Павлович (Eastern-European Journal of Enterprise Technologies, 2013)
The estimation of reserve of a heat carrier in the primary coolant circuit of the reactor plant with the watermoderated water-cooled power reactor-1000 is one of the problems, which still have no comprehensive solution. To indicate the level of the heat carrier it is suggested to use thermoelectric level indicator at certain marks of the reactor, which works according to the heat-loss anemometer principle. In the suggested structure of measurement the level indicator works in constant current mode. The studies provide the static and dynamic characteristics of the indicator. The modes of heating were studied; the algorithms, which provide the operability of the indicator and the method of the level indication, were worked out. The studies are being carried out in order to improve and optimize the algorithmic and mathematical support of the method; other possible structures of measurements are being analyzed to improve the reliability of its operation.